Two decades of off-pump coronary artery bypass surgery: Harefield experience - Raja, Shahzad G. (Journal of Thoracic Disease, 2016)
The morbidity and mortality associated with conventional coronary artery bypass grafting (CABG) attributed to invasiveness of cardiopulmonary bypass (CPB) has been well documented. Recognition of this invasiveness with a focus centered on abolishing, or at least reducing the CPB associated morbidity and mortality led to the resurgence of off-pump coronary artery bypass (OPCAB) surgery nearly two decades ago. At about the same time, OPCAB was adopted at Harefield hospital partly as an institutional drive to promote innovation and partly as a strategy to improve outcomes. What was deemed as a challenging technique initially and practiced by a single surgeon has now become a valid substitute to conventional CABG for achieving complete myocardial revascularization. This strategy now accounts for more than 50% of all coronary artery surgery operations at Harefield hospital and is systematically used to treat all coronary anatomies; achieve complete revascularization by accessing all territories subtended by main coronary arteries; and accomplish equivalent quality grafts without restriction in vascular conduit usage. This review article provides an overview of the evolution of OPCAB surgery at an institution with a well-established OPCAB program confirming that as surgeons’ experience matures, OPCAB surgery permits safe and effective total myocardial revascularization in virtually all patients with multivessel coronary artery disease.